1987
DOI: 10.1037/0012-1649.23.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Parents' responses to the emotional distress of their children: Relations with children's competence.

Abstract: Although investigators have proposed in various theories that the socialization of emotions has important implications for children's general competence, very little empirical data exist. In the present study, parents' responses to the emotional distress of their preschool children were examined in the context of more general dimensions of parenting (warmth and control), and the relation of these responses to children's competence was assessed. Data on parent-child interactions were collected for 30 families, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
176
1
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(211 citation statements)
references
References 28 publications
30
176
1
4
Order By: Relevance
“…Research by Flaks and colleagues (1995) substantiates what we found in our study, namely that children in heterosexual families do not differ from children in lesbian families in terms of problem behavior. Our result is in line with the view of Roberts and Strayer (1987), who assume that higher levels of warmth and parental involvement do not result in increasing levels of well being of a child once a certain threshold has been passed. Our findings are also in line with the results among other parents who also have go through great lengths before they could fulfill their wish to create a family, such as IVF, AID, and adoptive parents (Golomok et al, 1995;Van Balen, 1998).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Research by Flaks and colleagues (1995) substantiates what we found in our study, namely that children in heterosexual families do not differ from children in lesbian families in terms of problem behavior. Our result is in line with the view of Roberts and Strayer (1987), who assume that higher levels of warmth and parental involvement do not result in increasing levels of well being of a child once a certain threshold has been passed. Our findings are also in line with the results among other parents who also have go through great lengths before they could fulfill their wish to create a family, such as IVF, AID, and adoptive parents (Golomok et al, 1995;Van Balen, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…However, positive or negative consequences in psychological development of the child have not yet been established. It may be that increasing levels of warmth and parental involvement do not result in increasing levels of child well being once a certain threshold is passed (Roberts, 1986;Roberts & Strayer, 1987). On the other hand, the studies reviewed have shortcomings.…”
Section: Conclusion and Limitationsmentioning
confidence: 91%
“…b n ϭ 33 for boys; n ϭ 21 for girls. research has not found gender differences in sadness and anxiety in this age group (e.g., Hinde, Tamplin, & Barrett, 1993;Roberts & Strayer, 1987). We may have found differences because this competitive game task, in which children experienced the anticipation of waiting for the tower of blocks to fall and the failure of having their own tower fall, elicited a range of sad and anxious expressions, enabling us to observe gender differences.…”
Section: Gender Differences In Children's Emotion Expressionmentioning
confidence: 90%
“…A caregiver appears to provide ''scaffolding'' (e.g., Denham, Mason, & Couchoud, 1995) or structure that enables and fosters a child's emotional development. Examples of this phenomenon include (a) coregulation of infant emotion that is sensitive to the infant's (e.g., temperamental) needs, (b) coconstruction of emotion narratives by mother-child dyads that may serve as later emotion ''scripts'' for the child, and (c) maternal encouragement of autonomy as the child learns how to regulate independently of the mother (e.g., Calkins, 1994;Calkins & Johnson, 1998;Casey & Fuller, 1994;Denham, Renwick, & Holt, 1991;Eisenberg et al, 1999;Feldman, Greenbaum, & Yirmiya, 1999;Grolnick, Kurowski, McMenamy, Rivkin, & Bridges, 1998;Kobak, Cole, Ferenz-Gillies, Fleming, & Gamble, 1994;Oppenheim, Nir, Warren, & Emde, 1997;Roberts & Strayer, 1987).…”
Section: Other Emotion Regulation Processes: Normative Populationsmentioning
confidence: 99%